Predictors of Anxiety toward COVID-19 Delta Variant: A Cross- Sectional Study among Healthcare Providers in Java and Bali, Indonesia - Swarjana, I Ketut; Putu Darma Suyasa, I Gede; Nuryanto, I Kadek (UI Scholars Hub, 2022)
Health facilities are experiencing overcapacity, oxygen scarcity, and a limited number of healthcare providers due to the coronavirus disease 2019 (COVID-19), thus impacted on anxiety. This study aimed to determine predictors of anxiety among healthcare providers toward the Delta variant of COVID-19 in Indonesia. A cross-sectional study was conducted with 371 healthcare providers in Java and Bali Islands, and the snowball sampling technique was used. Data were collected using a questionnaire and distributed through social media (WhatsApp), then analyzed using univariate analysis, bivariate analysis (Chi-square test), and multivariate analysis (multiple logistic regression). The results showed that 81 (21.8%) respondents experienced anxiety. The workplace (AOR: = 0.617; p-value = 0.011), a history of confirmed positive for COVID-19 (AOR = 2.965; p-value<0.001), and the respondent's comorbidities (AOR = 8.753; p-value<0.001) were significantly associated with anxiety toward the Delta variant. Healthcare managers must regularly evaluate the psychological condition of their subordinates during the COVID-19 pandemic so that anxiety can be detected and overcome early through constructive self-adaptation and positive coping mechanisms.